Negotiation Between Parents and Children in Choosing a Marriage Partner: An Islamic Legal Perspective on Kafa'ah and Maslahah Mursalah - Sabri, Fahruddin Ali (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
The choice of a life partner in Muslim society involves not only individual preferences but is also influenced by family roles and considerations. This study aims to analyze the negotiation process between parents and children in determining a life partner in Babadan District, Ponorogo, and to review it from the perspectives of kafa'ah and maslahah mursalah. This study uses ethnographic methods to obtain an overview of women's experience and knowledge in choosing a life partner. Data were obtained through interview techniques and documentation of eight informants, consisting of parents, youth, and community leaders, who were selected purposively. Data analysis was conducted using a descriptive-analytical approach within an interactive analysis model. The results of the study show that the process of choosing a partner involves negotiations between parents and children, influenced by religious values, economic conditions, family background, and social traditions that develop within society. Parents tend to consider reciprocity (kafa'ah), especially in terms of religiosity, economic responsibility, and the prospective spouse's social background. Meanwhile, children's involvement indicates a shift toward more dialogical decision-making in the family. From the perspective of maslahah mursalah, the negotiation process reflects efforts to realize the family's benefits and maintain harmony and stability in domestic life.